Gerakan Orientalisme dan Gereja Methodist Episcopal (GME) Terhadap Penduduk Islam: Analisis Pensejarahan di Malaysia Abad ke-19 dan 20: Movement of Orientalism and the Methodist Episcopal Church (GME) against the Muslim Population: A Historiographical Analysis of Malaysia in 19th and 20th Century - Aziz, H.,; Zakariya, H.,; Rahman, A. H. A.,; Salamun, H.,; Ismail, I. L. M.,; Said, S.,; Sulaiman, R.,; Hamdan, A. N., (Global Journal Al-Thaqafah, 2024)
The 19th and 20th centuries saw intensive efforts by the Orientalist movement and the Methodist Episcopal Church (GME) to change the beliefs of the Muslim population in Malaysia. This article analyzes the strategies employed by Orientalists and GME in achieving their goals. Utilizing a historical approach and drawing from archival data, missionary documents, and secondary sources, the study presents its findings in a descriptive form. The research reveals that Orientalism introduced a new narrative to the culture and religion upheld by the population through the lens of stereotypes and generalizations. In contrast, GME sought to engage the Muslim population through dialogue and education, all while operating within the framework of Christian missionary efforts. Despite these attempts to alter the identity of the Muslim homeland, GME was largely unsuccessful, facing a population that was already structurally resilient due to the teachings of Islam. Influential groups within the community, such as religious teachers, hajj, and lebai played a dominant role in maintaining Islamic traditions. Among these, individuals who have completed the Hajj are particularly noteworthy, as they tend to demonstrate unwavering commitment to Islam and enjoy a relatively high social status.